2020
DOI: 10.1016/j.eng.2020.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Next Generation of Retinal Neuroprosthesis: Visual Computation with Spikes

Abstract: Neuroprosthesis, as one type of precision medicine device, is aiming for manipulating neuronal signals of the brain in a closed-loop fashion, together with receiving stimulus from the environment and controlling some part of our brain/body. In terms of vision, incoming information can be processed by the brain in millisecond interval. The retina computes visual scenes and then sends its output as neuronal spikes to the cortex for further computation. Therefore, the neuronal signal of interest for retinal neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 191 publications
0
26
0
Order By: Relevance
“…The retina has been thought of as a relatively simple neuronal circuit, however, it has been suggested that many complex computations can be realized by their neurons, in particular, the RGCs [11]. It has been studied intensively to develop various types of models for the encoding of visual scenes in the retina [1,13,16]. Similar to our current study, other recent work also focuses on neuronal spikes in the retina to develop the novel decoding methods [17,24,25].…”
Section: Implication For Other Neuronal Systemsmentioning
confidence: 76%
See 1 more Smart Citation
“…The retina has been thought of as a relatively simple neuronal circuit, however, it has been suggested that many complex computations can be realized by their neurons, in particular, the RGCs [11]. It has been studied intensively to develop various types of models for the encoding of visual scenes in the retina [1,13,16]. Similar to our current study, other recent work also focuses on neuronal spikes in the retina to develop the novel decoding methods [17,24,25].…”
Section: Implication For Other Neuronal Systemsmentioning
confidence: 76%
“…Various neuroscience mech-anisms have been identified in understanding the retinal computation of visual scenes by its neurons and neural circuitry [6,7,8,9,10,11]. In addition, for understanding the encoding principles of the retina, a number of models are developed based on different properties of neurons and neural circuits in the retina [12,13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…As discussed in [32], we can assume that the actual firing ratê r i (t) is linearly related to the "firing rate" r i (t) obtained from Eq. (16), that is,…”
Section: Implementation Of Inference With Neural Networkmentioning
confidence: 99%
“…Or more precisely, how a network of spiking neurons in the brain can implement inference of probabilistic graphical models? This problem is of great importance to both computer science and brain science [16]. If we known the neural algorithms of probabilistic inference, it is possible to build a machine that can perform probabilistic inference like the human brain.…”
Section: Introductionmentioning
confidence: 99%
“…Even for the retina, a relatively simple neuronal circuit, the underlying structure and, in particular, its functional characteristics are still not completely understood. However, the retina serves as a typical model for both deciphering the structure of neuronal circuits [1], [2], [3], [4], [5], [6] and testing novel methods for neuronal coding [7], [8], [9], [10], [11]. The retina consists of three layers with photoreceptors, bipolar cells, and ganglion cells together with inhibitory horizontal and amacrine cells in between as illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%